Nutritional and Medicinal value of maize silk - Sapna, Sapna; Siddiqui, Waseem A (Indian Farming, 2017)
Corn silk has been used as diuretic, antilithiasic, uricosuric, and antiseptic. It is used for the treatment of edema as well as for cystitis, gout, kidney stones, nephritis, and prostatitis. These activities may be due to the presence of flavonoids, alkaloids, phenols, steroids, glycosides and tannins in corn silk.